A trematode parasite derived growth factor binds and exerts influences on host immune functions via host cytokine receptor complexes - Sulaiman, Azad A.; Zolnierczyk, Katarzyna; Japa, Ornampai; Owen, Jonathan P.; Maddison, Ben C.; Emes, Richard D.; Hodgkinson, Jane E.; Gough, Kevin C.; Flynn, Robin J. (Public Library of Science, 2016)
The trematode Fasciola hepatica is responsible for chronic zoonotic infection globally. Despite causing a potent T-helper 2 response, it is believed that potent immunomodulation is responsible for rendering this host reactive non-protective host response thereby allow- ing the parasite to remain long-lived. We have previously identified a growth factor, FhTLM, belonging to the TGF superfamily can have developmental effects on the parasite. Herein we demonstrate that FhTLM can exert influence over host immune functions in a host receptor specific fashion. FhTLM can bind to receptor members of the Transforming Growth Factor (TGF) superfamily, with a greater affinity for TGF-β RII. Upon ligation FhTLM initiates the Smad2/3 pathway resulting in phenotypic changes in both fibroblasts and macrophages. The formation of fibroblast CFUs is reduced when cells are cultured with FhTLM, as a result of TGF-β RI kinase activity. In parallel the wound closure response of fibroblasts is also delayed in the presence of FhTLM. When stimulated with FhTLM blood monocyte derived macrophages adopt an alternative or regulatory phenotype. They express high levels interleukin (IL)-10 and arginase-1 while displaying low levels of IL-12 and nitric oxide. Moreover they also undergo significant upregulation of the inhibitory recep- tor PD-L1 and the mannose receptor. Use of RNAi demonstrates that this effect is depen- dent on TGF-β RII and mRNA knock-down leads to a loss of IL-10 and PD-L1. Finally, we demonstrate that FhTLM aids newly excysted juveniles (NEJs) in their evasion of antibody- dependent cell cytotoxicity (ADCC) by reducing the NO response of macrophages—again dependent on TGF-β RI kinase. FhTLM displays restricted expression to the F. hepatica gut resident NEJ stages. The altered fibroblast responses would suggest a role for damp- ened tissue repair responses in facilitating parasite migration. Furthermore, the adoption of a regulatory macrophage phenotype would allow for a reduced effector response targetingjuvenile parasites which we demonstrate extends to an abrogation of the ADCC response. Thus suggesting that FhTLM is a stage specific evasion molecule that utilises host cytokine receptors. These findings are the first to clearly demonstrate the interaction of a helminth cytokine with a host receptor complex resulting in immune modifications that facilitate the non-protective chronic immune response which is characteristic of F. hepatica infection.